Handbook of type 1 diabetes mellitus : etiology, diagnosis, and treatment - Aucoin, Leon; Prideux, Tristan (Metabolic diseases-laboratory and clinical research series, 2010)
Type I diabetes (T1D) is an autoimmune, and inflammatory disease. This book reviews and discusses the progress on environmental triggers and endogenous alarmins linking innate immunity to the pathogenesis of type 1 diabetes. It also examines the potential anti-inflammatory treatments for T1D evaluated in several models of the disease